Developing a model to strengthening base of collaboration in local governance through participatory budgeting - Chinnasri, Walaiporn; Subnavin, Supanut (Modern Management Frontier Journal, 2024)
This research article aims to: 1) study the problems in order to analyze the development of a model to strengthen the network base of cooperation in local governance through participatory budgeting. 2) study the contributions of management based on cooperation and participatory budgeting that help strengthen local governance. This study employed qualitative research methods using participatory community analysis techniques (Participatory Rural Appraisal: PRA) with in-depth interviews and small group discussions. The key informants were local government organization leaders, community leaders in the study area, public sector/civil society network, private network, government network, and academic and educational institution network totaling 60 people and Five scholars. The results of the study revealed that the challenges in developing cooperation include: 1) unfavorable regulations and laws 2) a lack of a cooperative culture among the public 3) a lack of motivation and skills in fostering cooperation and 4) the absence of leadership in promoting collaboration. The recommended approaches to enhance cooperation are: 1) involving relevant networks in joint roles 2) establishing mechanisms, regulations, rules, and mutual agreements 3) building trust to ensure transparent management and 4) the role of leadership in collaboration. Therefore, recognizing the significance of strong cooperation as the foundation of local governance through participatory budgeting leads to increased collaboration.